Normal plasma lipoproteins and fertility in gene-targeted mice homozygous for a disruption in the gene encoding very low density lipoprotein receptor. - Frykman, P K (1995)
The very low density lipoprotein (VLDL) receptor is a recently cloned member of the low density lipoprotein (LDL) receptor family that mediates the binding and uptake of VLDL when overexpressed in animal cells. Its sequence is 94% identical in humans and rabbits and 84% identical in humans and chickens, implying a conserved function. Its high level expression in muscle and adipose tissue suggests a role in VLDL triacylglycerol delivery. Mutations in the chicken homologue cause female sterility, owing to impaired VLDL and vitellogenin uptake during egg yolk formation. We used homologous recombination in mouse embryonic stem cells to produce homozygous knockout mice that lack immunodetectable VLDL receptors. Homozygous mice of both sexes were viable and normally fertile. Plasma levels of cholesterol, triacylglycerol, and lipoproteins were normal when the mice were fed normal, high-carbohydrate, or high-fat diets. The sole abnormality detected was a modest decrease in body weight, body mass index, and adipose tissue mass as determined by the weights of epididymal fat pads. We conclude that the VLDL receptor is not required for VLDL clearance from plasma or for ovulation in mice.